ARTRITE REUMATRHEUMATOID ARTHRITIS: CLINICAL OVERVIEW AND IMPACTS ON QUALITY OF LIFE DAOIDE: VISÃO GERAL CLÍNICA E IMPACTOS NA QUALIDADE DE VIDA (CIPEEX, 2025)
Rheumatoid arthritis (RA) is a chronic, systemic, autoimmune inflammatory disease that mainly affects the synovial joints and can cause deformities and functional loss. It mainly affects women of childbearing age and has a significant physical and psychosocial impact. This study aims to present an overview of rheumatoid arthritis, covering its pathophysiology, symptoms, diagnosis, treatment, and consequences for patients' quality of life. A bibliographic search was conducted based on scientific articles and updated academic materials obtained from the PubMed and SciELO databases, addressing the main clinical and therapeutic aspects of RA. Recent published studies addressing the clinical, diagnostic, and therapeutic aspects of the disease were selected. The results showed that RA has a multifactorial etiology, involving genetic predisposition, hormonal, and environmental factors. Symptoms include pain, morning stiffness, joint edema, and systemic manifestations. The diagnosis is based on clinical laboratory criteria such as rheumatoid factor, anti-cyclic citrullinated peptide antibodies, C-reactive protein, erythrocyte sedimentation rate, and imaging tests. Treatment aims to control inflammation and pain using anti-inflammatory drugs, corticosteroids, disease-modifying antirheumatic drugs (DMARDs), and biological agents, in addition to physical therapy and multidisciplinary follow-up. The disease significantly affects quality of life, requiring ongoing support for emotional and functional management. Although incurable, RA can be controlled with proper treatment and early diagnosis, preventing deformities and promoting well-being. The approach should be individualized and integrated, involving multiple health professionals to ensure improved functionality and comfort for patients.
Keywords: artrite reumatoide; doenças autoimunes; inflamação crônica; perda funcional